National Basketball Association Franchises: Team Performance and Financial Success - Jozsa, Frank P. (Lexington Books, 2017)
This book examines the development and organization of the NBA and its clubs, how each club has performed in seasons and postseasons, and to what extent each has prospered and succeeded as a business enterprise despite competition for market share from other types of entertainment. Each chapter contains two core themes—Team Performance and Franchise Business. The former highlights how teams won division and conference titles and NBA championships while the latter analyzes and compares financial data including revenue, gate receipts, and operating income. The book also explores such things as when each franchise organized and why it joined the NBA, a brief profile of its current majority owner or ownership group, records of teams’ special coaches and players, attendances at home games, and how their arenas rank as venues for fans. This book explains why particular teams located in very large, large, midsized, or small markets win more games and titles than others and when and how frequently this occurs. In addition, it provides ways to individually—and by division or conference—compare basketball franchises from a financial perspective.